Styles and learning strategies, an effective search to find the relationship with academic motivation - Vargas, Kleiber (2019)
The objective was to analyze the relationship between the academic motivation and the learning styles of the students of the Primary Education Program of the National University of Puno Altiplano in the academic semester 2017. The research is of simple correlation type and of quantitative approach, the design of research follows the guidelines of the hypothetical deductive model. The work allowed to understand that the tendencies that they manage to internalize competences that will provide them with the optimum academic level to face their profession. The learning style has an emotional, affective and sentimental component that is decisive in the development of competences. The data was obtained by processing in the SPSS program. The results indicate that there is a 0.95 ratio between the variables studied.